Enhancing Financial Literacy and Financial Guidance for the Self-Sufficient Republik Tani Kopi Mandiri Group in Kucur Village - Cahyadi, Rino Tam; Wijayanti, Dian; Brian Pratama, Bagas; Rohim, Yasin Nur (LPPM Universitas Ma Chung, 2024)
Financial reporting is a crucial aspect that every company must possess. Within a business, financial reports serve as the foundation for planning, control, and decision-making. The absence of accurate financial reports can significantly impact performance measurement within a company. Ignorance towards a business's performance is a problem that needs to be addressed. Business growth necessitates a systematic financial system. Republik Tani Kopi Mandiri (RTM) is one of the SMEs facing issues regarding financial reporting and cost of goods sold. Educating and assisting in the preparation of financial reports and cost of goods sold calculations are essential for SMEs, particularly RTM.